Museu, informação e comunicação: o processo de construção do discurso museográfico e suas estratégias - (:unkn) unknown (Universidade Federal do Rio de Janeiro / Instituto Brasileiro de Informação em Ciência e Tecnologia, 1999)
An exploratory analysis of the Information Science and Museology areas upon the constitution process of the museographic discourse and its exhibition strategies. This process is focused as an informational and communicational process, involving scientific and technical activities, in which are subjacent a team of concepts, ideas and visions of the world that inscrebes the signs of a contextual discourse - historical, social and culturally determined. This investigation deals with the concepts of information and discourse in order to reflect the web of possible meanings that constitutes the museum exhibition and its relation with the users. The work analises the exhibition as a communication space focusing museums that work with historical objects. the work aprproaches information not only as raw material but also viewed as a possility to transform cultural practices of the modern society. It deals with reflection upon the museological information as a phenomenon, which overpasses the object, the document, the discourse, and appears as an articulater of there multiple instances enabling the reflection, questioning and change
Keywords: Informação cultural; Museu; Exposição; CNPQ::CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO